A history of the Grahamstown Teachers' Training College 1894-1975 - Kelly, Leonard Eric (Rhodes University, Faculty of Humanities, Department of History, 2017)
In the Cape Colony, and then in South Africa generally, the twentieth century was to see the emergence, growth, and final closure of teacher training colleges. South Africa was one of the few Anglophone countries on the African Continent which, in 2003, did not have a separate and dedicated system of Teacher Education Colleges.1 From the 1920s on, there was a spirited debate over whether primary school teacher training was better achieved in the training college or the university. The publication of the National Education Amendment Act (No 73 of 1969) finally placed all teacher training, primary/elementary and secondary, within University Faculties of Education. The present study investigates the history of the Grahamstown Teacher Training College (GTTC) which was officially recognised in 1894 for the training of young white women. The GTTC was an independent college, founded and owned by an Anglican Religious Community for women, the Community of the Resurrection of Our Lord (CR), but it was also an Aided College of the Cape Education Department. As an Aided College, the GTTC was subject to Government Inspection annually, and the students wrote the official examinations set by the Department of Education. The College was run entirely by women and existed for 81 years. The emphasis in the college was on the practical professional training offered. The focus was on the 'complete' education of the student, rather than merely on the content of the curriculum. This study shows that the GTTC more than earned its reputation of being one of the finest training colleges in South Africa and that it was indeed a unique educational development. A feature of particular note was that the college was a trail-blazer, a pioneer in the field of education practices. It was the first college to introduce class music and class singing, the first to employ a physical education teacher, to have a full-time librarian and elocutionist, and it was at the GTTC that the assignment method of study was introduced. All these factors are highlighted in the course of this study.
Keywords: Teachers Training of -- South Africa -- Makhanda -- History; Universities and colleges -- South Africa -- Makhanda -- History; Grahamstown (South Africa) -- Teachers' Training College; South Africa. National Education Policy Act, 1996; |Education, Higher -- South Africa -- Makhanda -- History -- 20th century